An Wavelet analysis of connectedness between volatility of the energy and other markets during the COVID-19 crisis - Le Thanh Ha (Energy Strategy Reviews, 2023)
By applying novel partial wavelet coherency, this paper investigates the transmission mechanism of the volatility from the oil, gold, and silver sector to the energy sector in the time and frequency dimensions as well as the influence of the COVID-19 health crisis on this linkage. The multiple coherencies suggest at least five multiple cycles, which are located at high frequencies (the 52 – 132-day frequency band). Among these cycles, the largest one occurs at the low frequency (the 120 – 132-day frequency band), and this cycle is persistently prolonged. Notably, the four sectors' remarkable interlinkages of the volatility are presented more clearly since the COVID-19 pandemic first appeared and hit the globe (from the end of 2019 to the middle of 2020). The partial coherency between the volatility of the energy sector and the volatility of the oil sector reveals that the relations between two sectors are relatively persistent, which changes in the energy sector's volatility cause the oil sector to become more volatile. The partial coherency between the volatility of the energy sector and the volatility of the gold and silver sector suggests their interlinkages are time-varying and can be divided into four phases. The relationships are either positive or negative, and the energy sector or the silver or gold sector could be an attendant of other market's rising volatility. During the time of the COVID-19 pandemic, the energy sector's volatility is in-phase with the oil and silver sector's volatility leading, whilst the gold sector's volatility leads to the energy sector's volatility, and the relation is negative.